Changing routine activities and the decline of youth crime: A repeated cross-sectional analysis of self-reported delinquency in Sweden, 1999-2017 - Svensson, Robert (Criminology, 2021)
This study examines the declining crime trend among Swedish adolescents between 1999 and 2017 using data from eight repeated cross-sectional waves of a nationally representative school survey (N = ca. 49,000). We examined to what extent changes in parental monitoring, school bonds, attitudes toward crime, routine activities, and binge drinking were related to the noticeable decline in youth crime. Multilevel modeling was employed for the analysis of temporal trends. We found strong empirical support for our hypotheses, that is, that changes in social bonds, attitudes toward crime, and routine activities were all associated with the decline in youth crime. Routine activities had the strongest explanatory power, and all predictors combined accounted for most of the variance attributed to the decline in youth crime. This study moves research on the crime drop closer to the analysis of social mechanisms by demonstrating that micro-level associations between theoretically relevant, proximal variables, and delinquency account for macro-level change.